Adaptive reclosing strategy for single outgoing line of converter-interfaced wind park using distance relaying algorithm. (January 2021) - Wang, Ting; Song, Guobing; Hussain, Kazmi Sayed Tassawar
Highlights: An adaptive auto-reclosing scheme for converter-interfaced wind park. Improved distance relaying algorithm, not influenced by high fault impedance and infeed/outfeed effect. Active detection and independent judgements to realize the fault identification. No additional equipment needed for active injection. Abstract: The 110 kV single outgoing line powered by wind generation usually adopts tripolar tripping and three-phase auto-recloser. The electrical quantities of the single line attenuate quickly after fault tripping, which makes it difficult to identify fault properties during the dead time. Also, due to the high voltage or frequency protection, the converter-interfaced wind generation is prone to be blocked after tripolar tripping. The machine-side circuit breaker is then reclosed temporarily. A fast adaptive auto-reclosing scheme is proposed for three-phase tripping scenarios by injecting sinusoidal currents from interface converter to the faulty line. By re-activating pulse width modulation (PWM) for a very short time, the interface converter works as STATCOM to regulate the output voltage and then an active current injection is realized. Improved distance relaying algorithm is deduced in this injection scenario to locate the fault and achieve fault property identification. After the confirmation of arc extinction, the triggering control of interface converter will be re-activated and the circuit breaker will be reclosed to restore power transmission. The proposed fast three-phase reclosing scheme is validated in PSCAD/EMTDC and the simulation results show the accuracy of fault identification and short reclosing time.